2020
DOI: 10.1016/j.radonc.2020.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Dose-averaged linear energy transfer per se does not correlate with late rectal complications in carbon-ion radiotherapy

Abstract: Background and purpose: Several studies have focused on increasing the linear energy transfer (LET) within tumours to achieve higher biological effects in carbon-ion radiotherapy (C-ion RT). However, it remains unclear whether LET affects late complications. We assessed whether physical dose and LET distribution can be specific factors for late rectal complications in C-ion RT. Materials and methods: Overall, 134 patients with uterine carcinomas were registered and retrospectively analysed. Of 134 patients, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…The dose constraints for the D2cc of the intestine and bladder were set at 50 Gy (RBE) and 60 Gy (RBE) in 16 fractions, respectively, and at 60 Gy (RBE) and 70 Gy (RBE) when combined with the dose distribution of the previous XRT, based on prior evaluations by Okonogi et al 15 and Kim et al 16 Examples of PTV with isodose distributions are shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The dose constraints for the D2cc of the intestine and bladder were set at 50 Gy (RBE) and 60 Gy (RBE) in 16 fractions, respectively, and at 60 Gy (RBE) and 70 Gy (RBE) when combined with the dose distribution of the previous XRT, based on prior evaluations by Okonogi et al 15 and Kim et al 16 Examples of PTV with isodose distributions are shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 16 , 17 Furthermore, several recent studies have demonstrated the potential association of LETd of CIRT with tumour recurrence or normal tissue toxicities. 9 , 10 , 11 These suggest that clinical outcomes could be further improved by incorporating LETd in the planning optimization process. Although LETd can be derived through MC simulation, 18 measurements, 12 or analytic calculations, 19 evaluation or optimization of LETd in patients’ treatment plans remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…8 LETd also has been acknowledged as an indicator strongly correlated to the clinical outcome in cancer radiotherapy. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okonogi and colleagues similarly considered uterine cancer, focusing on whether LET was correlative with late rectal toxicity rate ( 49 ). In evaluating 132 patients with CIRT-treated uterine carcinoma and greater than 6 months of follow-up, nine were noted to have grade 3 or 4 late rectal complications.…”
Section: Let and Rbementioning
confidence: 99%